Interview mit Ulli und Georgina Beier, und Jonathan Ritchie (Of Art Worlds - Collecting and Archiving Modern and Contemporary Art on the African Continent, 2009)
Copyright held by Iwalewahaus, CBCIU.
Keywords: Interviews; Artists; Nigeria; Papua New Guinea; New Guinea; Art Collector; Art Collecting